Silver-Containing α-MnO2 Nanorods: Electrochemistry in Rechargeable Aqueous Zn-MnO2 Batteries. Issue 15 (23rd October 2019) - Wang, Lei; Wu, Qiyuan; Abraham, Alyson; West, Patrick J.; Housel, Lisa M.; Singh, Gurpreet; Sadique, Nahian; Quilty, Calvin D.; Wu, Daren; Takeuchi, Esther S.; Marschilok, Amy C.; Takeuchi, Kenneth J.
Abstract : The reduction and subsequent oxidation of silver hollandite nanorods, Ag1.5 Mn8 O16, were explored in aqueous ZnSO4 electrolyte for the first time. The impact of reduction on the electrodes was probed where images of recovered cathodes were collected to evaluate the changes in morphology, structural, and electrochemical properties as a function of varying potential. Ag metal particle formation upon reduction was observed on reduction through a reduction-displacement reaction as confirmed by SEM/EDS, XRD, and XAS results accompanied by a decrease in charge transfer impedance, as determined by electrochemical impedance spectroscopy. On charge, in contrast to the reduction/oxidation electrochemistry in non-aqueous media where irreversible formation of silver metal was observed, disappearance of the silver metal is observed indicating oxidation of the silver centers is facilitated in aqueous electrolyte.